El gobierno colonial de Lima y su capacidad de manejo de la crisis frente al terremoto de 1687: respuestas del virrey y del cabildo secular - Mansilla, Judith (Revista del Instituto Riva-Agüero, 2016)
In the last decades, scholars have debated about the traditional representation of the Spanish administration during the seventeenth century as inefficient and impotent. Some of them even argue that the last Habsburg king’s regime was one of total decadence and inefficiency. Contrary to thisimage, the royal administrators of Lima, capital of the Peruvian Viceroyalty, showed great organizational and crisis management capacity after an intense earthquake, followed by a tsunami, hit the city and its port in 1687. In the midstof the chaos and destruction caused by the natural disaster, the viceroy and themembers of the city council were able to manage the limited resources at handand provide material and spiritual assistance to the increasing demands of Lima population.